Comparison of Clinical Safety and Outcomes of Early versus Delayed Laparoscopic Cholecystectomy for Acute Cholecystitis: A Meta-Analysis - Min-Wei Zhou; Xiao-Dong Gu; Jian-Bin Xiang; Zong-You Chen (The Scientific World Journal)
Objective. To compare the clinical safety and outcomes of early laparoscopic cholecystectomy versus delayed laparoscopic cholecystectomy for acute cholecystitis. Methods. Pertinent studies were selected from the Medline, EMBASE, and Cochrane library databases, references from published articles, and reviews. Seven randomized controlled trials (early laparoscopic cholecystectomy versus delayed laparoscopic cholecystectomy) were selected. Conventional meta-analysis according to Cochrane Collaboration was used for the pooling of the results. Results. Seven trials with 1106 patients were included. There was no significant difference between the two groups in terms of bile duct injury (Peto odds ratio 0.49 (95% confidence interval 0.05 to 4.72); P=0.54) or conversion to open cholecystectomy (risk ratio 0.91 (95% confidence interval 0.69 to 1.20); P=0.50). The total hospital stay was shorter by 4 days for early laparoscopic cholecystectomy (mean difference −4.12 (95% confidence interval −5.22 to −3.03) days; P<0.00001). Conclusion. Early laparoscopic cholecystectomy during acute cholecystitis is safe and shortens the total hospital stay.